General practitioners' attitude toward early and pre‐dementia diagnosis of AD in five European countries—A MOPEAD project survey. Issue 1 (23rd February 2021) - Sannemann, Lena; Müller, Theresa; Waterink, Lisa; Zwan, Marissa; Wimo, Anders; Stomrud, Erik; Pinó, Susana; Arrufat, Jordi; Rodríguez‐Gomez, Octavio; Benaque, Alba; Bon, Jaka; Ferreira, Daniel; et al.
Abstract: Introduction: General practitioners (GPs) play a key role in early identification of dementia, yet diagnosis is often missed or delayed in primary care. As part of the multinational Models of Patient Engagement for Alzheimer's Disease project, we assess GPs' attitude toward early and pre‐dementia diagnosis of AD and explore barriers to early diagnosis. Methods: Our survey covered general attitude toward early diagnosis, diagnostic procedures, resources, and opinion on present and future treatment options across five European countries. Results: In total 343 GPs completed the survey; 74% of GPs indicated that an early diagnosis is valuable. There were country‐specific differences in GPs' perceptions of reimbursement and time available for the patient. If a drug were available to slow down the progression of AD, 59% of the GPs would change their implementation of early diagnosis. Discussion: Our findings provide insight into GPs' attitudes by exploring differences in perception and management of early diagnosis.